Raspberry Pi robotic blueprints : utilize the powerful ingredients of Raspberry Pi to bring to life amazing robots that can act, draw, and have fun with laser tag /: utilize the powerful ingredients of Raspberry Pi to bring to life amazing robots that can act, draw, and have fun with laser tag. (2015) - Grimmett, Richard
No abstract available